Dynamics of the high-current ion beam in a section of the linear induction accelerator - Karas, V.I.; Kornilov, E.A.; Manuilenko, O.V.; Tarakanov, V.P.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2015)
The dynamics of the high-current ion beam (HCIB) in a section of the linear induction accelerator (LIA), consisting of magneto-isolated accelerating gap and the two drift spaces, is studied. In the most suitable variant of the HCIB compensation by accompanying and colliding beams of electrons, the current of the ion beam at the exit of first drift gap is close to the original.The optimization of the system parameters (the value of magnetic field produced by the coils with opposing currents, the size of the system, the parameters of the beams) at which a uniform the length of the gap acceleration of the HCIB is achieved, has been carried out. Wherein the quality of the ion beam at the exit of the LIA section is kept acceptable for heavy-ion inertial fusion.